π-Extended Ladder-Type Conjugated Polymers via BN-Annulation - Qiang, Peirong; Sun, Zuobang; Xue, Bai; Zhang, Fan (Organic Materials, 2021)
Two kinds of ladder-type conjugated polymers were concisely synthesized by the formation of single-stranded conjugated polymers via Stille cross-couplings, followed by nitrogen-directed electrophilic borylations at electron-rich aromatic rings. The resulting BN-annulated polymers show good film-forming behaviors and high air and thermal stability. Their structurally shape-persistent rigid backbones render them with π-extended conjugation, allowing for efficient light harvesting in the low-energy regions, and emitting strong fluorescence with narrow emission widths.
Keywords: ladder-type polymers; BN-annulation; π-extended conjugation; light harvesting; fluorescence emission